The main duties and professional activities of a medical nurse in a therapeutics department - Sivolap, V. V.; Likhasenko, I. V.; Oleynik, A. I.; Avramenko, N. F.; Gerasko, M. P.; Kurilets, L. O.; Сиволап, Віталій Вікторович; Лихасенко, Іветта Валеріївна; Олiйник, Олександр Iванович; Авраменко, Наталя Федорівна; Герасько, Марина Петрівна; Курілець, Лілія Олегівна (Zaporozhye state medical university, 2016)
The program of study of educational discipline "Nursing Practice" prepared in accordance with the educational and vocational training programs "specialist" direction 1201 "Medicine" specialty 7.12010001 "General medicine and 7.12010002 "Pediatrics", the curriculum, approved by the Ministry of Health of Ukraine № 414 of 23.07. 2007. The subject of study of discipline on the 3rd course is to acquire theoretical knowledge, practical skills and mastering the ability to module 1 "The main duties and professional activities of medical nurse in therapeutic department".